(3eYjf GdMcGe ajeG jJQOO Hjf GdNUejf ef GdCMcGes - (3Ydj Hf Ndjd GdWQGHdSj, CHh GdMSf, YdGA GdOjf,J (B844 (3g` s ((3eMeO Hf RcQjG GdeDPf s)
(3ChdgG (B:s
(3JHGQc GdPi CHOY GdehLhOGJ hdeG cGf Yde GdbVGA ef CLd GdYdhe bOQkG dCf Yde GdbVGA jaJbQ Edi eYQaI CMcGe JLQi eLQi GdcdjGJ s
(3BNQgG (B:s
(3hdbO CSeYJ ef fGOjJ , hCgOjJ Edi ef fhjJ hGdMeO ddg GdYdi GdZahQ hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hGdJGHYjf hSde JSdjekG s
(3GdfSNI HgG MhGTs
(3HChdgG Jedc HGSe GdMGL eMeO SdWGf eDQN SfI (B1282(3g`s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfGhjjf QDhS GdcdGe HGdMeQI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B286 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B88s
Keywords: (3Gdabg GdESdGejs